Lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst as well as preparation method and application thereof
Through the lanthanide metal-modified cobalt/concave-concave-rodite-based titanium silicate catalyst, the problem of insufficient catalytic activity and selectivity of existing cobalt catalysts is solved, and efficient lignin depolymerization and guaiacol production are achieved, with high economic benefits and good industrial application prospects.
Patent Information
- Application Number
- CN202411792079.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing cobalt catalysts have low catalytic activity when catalyzing the depolymerization of lignin and have low selectivity for guaiacol.
Using a lanthanide metal modified cobalt/concave-corrosalt-based titanium silicate catalyst, a catalyst with high catalytic activity and selectivity is formed by combining cobalt and lanthanide metals (such as cerium, lanthanum, samarium) with a concave-corrosalt-based titanium silicate support.
Under the water, glycerol and formic acid solvent system, no additional hydrogen source is required to achieve a lignin conversion rate of 100%, the guaiocorol yield is greater than 25%, and the guaiocorol product yield is greater than 75%, which has high economic benefits and good industrial application prospects.
Smart Images

Figure CN119588415A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lignin depolymerization, and in particular to a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst and a preparation method and application thereof. Background Art
[0002] Biomass is any organic matter and its metabolites produced by organisms, and is the only renewable organic carbon resource in nature. Among them, lignin is an amorphous polymer composed of phenylpropane units connected by CC and CO bonds, and is the main component of lignocellulosic biomass. Converting lignin into biofuels and compounds can alleviate the current energy pressure.
[0003] The catalytic depolymerization of lignin to obtain chemicals by pyrolysis, catalytic acid hydrolysis or alkaline hydrolysis and hydrogenation treatment is currently a hot topic. Among them, hydrodeoxygenation is one of the most common and effective methods for depolymerizing lignin into phenols and chemicals. Guaiacol is often present in lignin oil extracts, which are characterized by the presence of methoxyl and phenolic hydroxyl groups typical of lignin.
[0004] Transition metal cobalt is cheap compared to precious metals and has good lignin CC / CO decomposition and hydrogenation capabilities, so it has been widely used in catalytic lignin conversion. However, its catalytic activity is still not ideal, and its selectivity for guaiacol is not high. Summary of the invention
[0005] The main purpose of the present invention is to provide a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst with stronger catalytic activity and higher selectivity for guaiacol, and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, comprising a carrier and an active component loaded on the carrier, wherein the carrier is attapulgite-based titanium silicalite, and the active component is cobalt and a lanthanide metal.
[0007] Furthermore, the content of cobalt is 10 wt %, the content of lanthanide metal is 1-10 wt %, and the balance is attapulgite-based titanium silicalite.
[0008] Furthermore, the lanthanide metal is cerium, lanthanum or samarium.
[0009] The present invention also provides a method for preparing the above-mentioned lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, comprising the following steps:
[0010] S1. Add the acid-treated attapulgite to a tetrapropylammonium hydroxide aqueous solution, stir and treat to obtain a colorless transparent solution, which is recorded as solution A; add tetrabutyl titanate to isopropanol, mix well, then add the tetrapropylammonium hydroxide aqueous solution, stir and treat to obtain a colorless transparent solution, which is recorded as solution B;
[0011] S2, mixing solution A and solution B, first stirring, then heating to remove alcohol, and then adding water for stirring and aging to obtain an aged mixture;
[0012] S3, crystallizing the aged mixture, washing, drying and calcining the obtained product to obtain attapulgite-based titanium silicalite;
[0013] S4, mixing the cobalt precursor salt, the lanthanide metal precursor salt, the attapulgite-based titanium silicalite and the solvent, first stirring, then evaporating the solvent and drying, and finally calcining to obtain the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst.
[0014] Furthermore, in step (1), the mass volume ratio of the acid-treated attapulgite, tetrabutyl titanate and tetrapropylammonium hydroxide is 1 g: 0.1-0.5 ml: 2.5-5 g.
[0015] Furthermore, in step (2), the stirring treatment time is 1 to 2 hours; the heating temperature for removing alcohol is 80 to 90° C., and the time is 1 to 2 hours; and the stirring aging treatment time is 12 to 24 hours.
[0016] Furthermore, in step (3), the conditions for the crystallization treatment are a temperature of 150°C to 200°C and a time of 24 to 36 hours; the specific process of the calcination treatment is: heating the temperature in an air atmosphere at a rate of 1 to 5°C / min to 550 to 700°C, and then calcining at this temperature for 5 to 10 hours.
[0017] Furthermore, in step (4), the stirring treatment is carried out at room temperature for 6 to 12 hours; and the drying treatment is carried out at a temperature of 80 to 110° C. for 12 to 24 hours.
[0018] Furthermore, in step (4), the specific process of the calcination treatment is: heating the temperature to 500-700° C. at a heating rate of 1-5° C. / min in an air atmosphere, and then calcining at this temperature for 5-10 hours.
[0019] The present invention also provides the use of the above-mentioned lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst in catalyzing the depolymerization of lignin to prepare guaiacol.
[0020] The present invention also provides a method for preparing guaiacol by depolymerizing lignin, comprising the following steps: putting lignin, water, glycerol, formic acid and the above catalyst into a reactor, filling it with nitrogen and then conducting a sealed reaction.
[0021] Furthermore, the reaction conditions are temperature 210-310° C., stirring rate 400-600 r / min, and time 1-24 h.
[0022] The catalyst of the present invention adopts attapulgite-based titanium silicalite as a carrier, and cobalt and lanthanide metals (cerium, lanthanum and samarium) are combined as active components, which can enhance the ability of the catalyst to crack lignin; the attapulgite-based titanium silicalite has uniform and orderly microporous channels, a large specific surface area and ion exchange performance, and the molecular sieve has regular pores, high thermal stability and structural defects that can effectively disperse and anchor metals, inhibiting agglomeration and sintering.
[0023] Transition metal catalyst cobalt has a unique structure and properties. It is used in the hydrodeoxygenation reaction of lignin with its low cost and suitable hydrogenation activity. Cobalt-based metal catalysts have excellent performance in cracking CO / CC bonds and activating solvents. Lanthanide metals have efficient oxygen storage and release redox properties. Metal interactions lead to the generation of oxygen vacancies, and oxygen-rich vacancies can adsorb intermediates in a specific way. At the same time, the addition of lanthanide metals produces electron transfer between metals, which can improve the interaction between metals and carriers, which is beneficial to the hydrogenation ability of metal cobalt and the efficiency of catalytic depolymerization of lignin.
[0024] The beneficial effects of the present invention are embodied in:
[0025] The catalyst of the invention is used for catalytically depolymerizing lignin to prepare guaiacol. Under the conditions of water, glycerol and formic acid solvents, nitrogen atmosphere and no additional hydrogen source, a 100% lignin conversion rate can be achieved, a guaiacol yield of more than 25%, and a guaiacol product yield of more than 75%. The catalyst has high economic benefits and a small metal loading amount, can improve the catalyst's depolymerization ability and selectivity for lignin, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD spectrum of the attapulgite-based titanium silicalite prepared in Example 1.
[0027] Figure 2 This is the FTIR spectrum of the attapulgite-based titanium silicalite prepared in Example 1.
[0028] Figure 3 This is the N2 adsorption-desorption isotherm diagram of the attapulgite-based titanium silicalite prepared in Example 1.
[0029] Figure 4 This is the pore size distribution diagram of the attapulgite-based titanium silicalite prepared in Example 1.
[0030] Figure 5 The electron paramagnetic resonance (EPR) images of the attapulgite-based titanium silicalite, catalyst C1 and catalyst D1 prepared in Example 1 are shown.
[0031] Figure 6 This is the XRD spectrum of the final product of step S3 of comparative example 5. DETAILED DESCRIPTION
[0032] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0033] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0034] Example 1
[0035] Preparation of lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst
[0036] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10wt%, a cerium content of 1wt%, and the remaining component is a carrier attapulgite-based titanium silicalite. The preparation method is as follows:
[0037] S1. Place 20 g of attapulgite in 120 mL of 3.5 mol / L hydrochloric acid solution, treat at 170° C. for 12 h, then transfer to a hydrothermal synthesis reactor for hydrothermal treatment at 180° C. for 72 h, then centrifuge and wash, and then dry at 105° C. for 12 h to obtain acid-treated attapulgite;
[0038] 2.5 g of tetrapropylammonium hydroxide was mixed with 15 ml of deionized water, and then 2 g of acid-treated attapulgite was slowly added in batches at room temperature and a stirring speed of 500 r / min, and the stirring was continued at a stirring speed of 400 r / min for 2 h to obtain a colorless transparent solution, which was recorded as solution A;
[0039] 2.5 g of tetrapropylammonium hydroxide was mixed with 15 ml of deionized water, and then an ester solution consisting of 0.5 ml of tetrabutyl titanate and 10 ml of isopropanol was added, and the mixture was stirred at a stirring speed of 400 r / min at room temperature for 1 h to obtain a colorless transparent solution, which was recorded as solution B;
[0040] S2, solution A and solution B were mixed, stirred at room temperature at a stirring speed of 400 r / min for 1 h, then stirred at 80°C at a stirring speed of 400 r / min for 2 h to remove the alcohols generated in the process and the added isopropanol, and then deionized water was added to make the volume 30 ml, and stirred at room temperature at a stirring speed of 350 r / min for aging for 24 h to obtain an aged mixture;
[0041] S3, transferring the aged mixture to a reactor, crystallizing at 180°C for 36 hours, centrifuging the solid product, washing with deionized water, drying at 105°C for 12 hours, and finally calcining at 550°C in an air atmosphere at a heating rate of 3°C / min for 6 hours to obtain attapulgite-based titanium silicalite;
[0042] S4. Add 0.4938 g of cobalt nitrate hexahydrate to 50 mL of deionized water and stir evenly. Add 1 g of attapulgite-based titanium silicalite and stir evenly. Then add 0.0310 g of cerium nitrate hexahydrate. Stir at room temperature at a stirring speed of 400 r / min for 6 hours, evaporate the water at 80°C, and then dry at 80°C for 24 hours. Grind the dried solid into powder, heat the temperature to 500°C at a heating rate of 5°C / min in an air atmosphere and calcine at a constant temperature for 10 hours to obtain a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, numbered C1.
[0043] Example 2
[0044] Preparation of lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst
[0045] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10wt%, a cerium content of 5wt%, and the remaining component is a carrier attapulgite-based titanium silicalite. The preparation method is as follows:
[0046] S1, 3.0g of tetrapropylammonium hydroxide was mixed with 15ml of deionized water, and then 2g of attapulgite treated with acid (prepared by the same method as in Example 1) was slowly added in batches at room temperature and a stirring speed of 500r / min, and the mixture was stirred at a stirring speed of 400r / min for 2h to obtain a colorless transparent solution, which was recorded as solution A;
[0047] 3.0 g of tetrapropylammonium hydroxide was mixed with 15 ml of deionized water, and then an ester solution consisting of 0.6 ml of tetrabutyl titanate and 10 ml of isopropanol was added, and stirred at room temperature at a stirring speed of 400 r / min for 1 h to obtain a colorless transparent solution, which was recorded as solution B;
[0048] S2, solution A and solution B were mixed, stirred at room temperature at a stirring speed of 400 r / min for 1.5 h, then stirred at 90 ° C at a stirring speed of 400 r / min for 1 h to remove the alcohols generated in the process and the added isopropanol, and then deionized water was added to make the volume 30 ml, and stirred at room temperature at a stirring speed of 350 r / min for aging for 22 h to obtain an aged mixture;
[0049] S3, transferring the aged mixture to a reactor, crystallizing at 150°C for 32 hours, centrifuging the solid product, washing with deionized water, drying at 105°C for 12 hours, and finally calcining at 600°C in an air atmosphere at a heating rate of 1°C / min for 10 hours to obtain attapulgite-based titanium silicalite;
[0050] S4. Add 0.4938 g of cobalt nitrate hexahydrate to 50 mL of deionized water and stir evenly. Add 1 g of attapulgite-based titanium silicalite and stir evenly. Add 0.1550 g of cerium nitrate hexahydrate and stir at room temperature at a stirring speed of 400 r / min for 12 h. Evaporate the water at 80°C and then dry at 105°C for 12 h. Grind the dried solid into powder. Heat the temperature at a rate of 3°C / min to 500°C in an air atmosphere and calcine at a constant temperature for 6 h to obtain a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, numbered C2.
[0051] Example 3
[0052] Preparation of lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst
[0053] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10 wt%, a cerium content of 10 wt%, and the remaining component is a carrier attapulgite-based titanium silicalite. The preparation method is as follows:
[0054] S1, 3.5g of tetrapropylammonium hydroxide was mixed with 15ml of deionized water, and then 2g of acid-treated attapulgite (prepared by the same method as in Example 1) was slowly added in batches at room temperature and a stirring speed of 500r / min, and the mixture was stirred at a stirring speed of 400r / min for 2h to obtain a colorless transparent solution, which was recorded as solution A;
[0055] 3.5 g of tetrapropylammonium hydroxide was mixed with 15 ml of deionized water, and then an ester solution consisting of 0.8 ml of tetrabutyl titanate and 10 ml of isopropanol was added, and the mixture was stirred at a stirring speed of 400 r / min at room temperature for 1 h to obtain a colorless transparent solution, which was recorded as solution B;
[0056] S2, solution A and solution B were mixed, stirred at room temperature at a stirring speed of 400 r / min for 2 h, then stirred at 85 ° C at a stirring speed of 400 r / min for 1.5 h to remove the alcohols generated in the process and the added isopropanol, and then deionized water was added to make the volume 30 ml, and stirred at room temperature at a stirring speed of 350 r / min for aging for 20 h to obtain an aged mixture;
[0057] S3, transferring the aged mixture to a reactor, crystallizing at 170°C for 28h, centrifuging the solid product, washing with deionized water, drying at 105°C for 12h, and finally calcining at 650°C in an air atmosphere at a heating rate of 2°C / min for 8h to obtain attapulgite-based titanium silicalite;
[0058] S4. Add 0.4938 g of cobalt nitrate hexahydrate to 50 mL of deionized water and stir evenly. Add 1 g of attapulgite-based titanium silicalite and stir evenly. Add 0.3099 g of cerium nitrate hexahydrate and stir at room temperature at a stirring speed of 400 r / min for 8 h. Evaporate the water at 80°C and then dry at 90°C for 20 h. Grind the dried solid into powder. Heat the temperature to 550°C at a heating rate of 4°C / min in an air atmosphere and calcine at a constant temperature for 8 h to obtain a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, numbered C3.
[0059] Example 4
[0060] Preparation of lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst
[0061] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10wt%, a lanthanum content of 5wt%, and the remaining component is a carrier attapulgite-based titanium silicalite. The preparation method is as follows:
[0062] S1, 4.5g of tetrapropylammonium hydroxide was mixed with 15ml of deionized water, and then 2g of acid-treated attapulgite (prepared by the same method as in Example 1) was slowly added in batches at room temperature and a stirring speed of 500r / min, and the mixture was stirred at a stirring speed of 400r / min for 2h to obtain a colorless transparent solution, which was recorded as solution A;
[0063] 4.5 g of tetrapropylammonium hydroxide was mixed with 15 ml of deionized water, and then an ester solution consisting of 0.9 ml of tetrabutyl titanate and 10 ml of isopropanol was added, and the mixture was stirred at a stirring speed of 400 r / min at room temperature for 1 h to obtain a colorless transparent solution, which was recorded as solution B;
[0064] S2, solution A and solution B were mixed, stirred at room temperature at a stirring speed of 400 r / min for 1.5 h, then stirred at 90 ° C at a stirring speed of 400 r / min for 1 h to remove the alcohols generated in the process and the added isopropanol, and then deionized water was added to make the volume 30 ml, and stirred at room temperature at a stirring speed of 350 r / min for 18 h to obtain an aged mixture;
[0065] S3, transferring the aged mixture to a reactor, crystallizing at 200°C for 24h, centrifuging the solid product, washing with deionized water, drying at 105°C for 12h, and finally calcining at 700°C in an air atmosphere at a heating rate of 4°C / min for 5h to obtain attapulgite-based titanium silicalite;
[0066] S4. Add 0.4938 g of cobalt nitrate hexahydrate to 50 mL of deionized water and stir evenly. Add 1 g of attapulgite-based titanium silicalite and stir evenly. Add 0.1169 g of lanthanum nitrate hexahydrate and stir at room temperature at a stirring speed of 400 r / min for 10 h. Evaporate the water at 80°C and then dry at 100°C for 15 h. Grind the dried solid into powder. Heat the mixture to 600°C at a heating rate of 2°C / min in an air atmosphere and calcine at a constant temperature for 5 h to obtain a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, numbered C4.
[0067] Example 5
[0068] Preparation of lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst
[0069] The catalyst prepared in this embodiment has an active ingredient cobalt content of 10wt%, a samarium content of 5wt%, and the remaining component is a carrier attapulgite-based titanium silicalite. The preparation method is as follows:
[0070] S1, 5.0g of tetrapropylammonium hydroxide was mixed with 15ml of deionized water, and then 2g of acid-treated attapulgite (prepared by the same method as in Example 1) was slowly added in batches at room temperature and a stirring speed of 500r / min, and the mixture was stirred at a stirring speed of 400r / min for 2h to obtain a colorless transparent solution, which was recorded as solution A;
[0071] 5.0 g of tetrapropylammonium hydroxide was mixed with 15 ml of deionized water, and then an ester solution consisting of 1.0 ml of tetrabutyl titanate and 10 ml of isopropanol was added, and stirred at room temperature at a stirring speed of 400 r / min for 1 h to obtain a colorless transparent solution, which was recorded as solution B;
[0072] S2, solution A and solution B were mixed, stirred at room temperature at a stirring speed of 400 r / min for 2 h, then stirred at 80 ° C at a stirring speed of 400 r / min for 2 h to remove the alcohols generated in the process and the added isopropanol, and then deionized water was added to make the volume 30 ml, and stirred at room temperature at a stirring speed of 350 r / min for 16 h to obtain an aged mixture;
[0073] S3, transferring the aged mixture to a reactor, crystallizing at 190°C for 26 hours, centrifuging the solid product, washing with deionized water, drying at 105°C for 12 hours, and finally calcining at 600°C in an air atmosphere at a heating rate of 5°C / min for 9 hours to obtain attapulgite-based titanium silicalite;
[0074] S4. Add 0.4938 g of cobalt nitrate hexahydrate to 50 mL of deionized water and stir evenly. Add 1 g of attapulgite-based titanium silicalite and stir evenly. Add 0.1478 g of samarium nitrate hexahydrate and stir at room temperature at a stirring speed of 400 r / min for 9 hours. Evaporate the water at 80°C and then dry at 100°C for 14 hours. Grind the dried solid into powder, heat the mixture to 700°C at a heating rate of 1°C / min in an air atmosphere and calcine at a constant temperature for 5 hours to obtain a lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, numbered C5.
[0075] Comparative Example 1
[0076] Preparation of comparative catalysts
[0077] In this comparative example, a catalyst was prepared in the same manner as in Example 2, except that the addition of cerium nitrate hexahydrate was omitted, and a catalyst having a cobalt content of 10 wt % and attapulgite-based titanium silicalite as the remaining component was finally obtained, which was numbered D1.
[0078] Comparative Example 2
[0079] Preparation of comparative catalysts
[0080] In this comparative example, a catalyst was prepared in the same manner as in Example 2, except that the addition of cerium nitrate hexahydrate was omitted and the amount of cobalt nitrate hexahydrate was adjusted to 0.7408 g. A catalyst having a cobalt content of 15 wt % and attapulgite-based titanium silicalite as the remaining component was finally obtained, numbered D2.
[0081] Comparative Example 3
[0082] Preparation of comparative catalysts
[0083] In this comparative example, the catalyst is prepared according to the method of Example 2, with the only difference being that cerium nitrate hexahydrate is replaced by niobium oxalate hexahydrate, and the amount of niobium oxalate hexahydrate used is 0.2895 g. The final catalyst obtained has a cobalt content of 10 wt%, a niobium content of 5%, and the remaining component is attapulgite-based titanium silicalite, and is numbered D3.
[0084] Comparative Example 4
[0085] Preparation of comparative catalysts
[0086] In this comparative example, the catalyst is prepared according to the method of Example 2, with the only difference that cerium nitrate hexahydrate is replaced by zirconium nitrate hexahydrate, and the amount of zirconium nitrate hexahydrate used is 0.2353 g. The final catalyst obtained has a cobalt content of 10 wt%, a zirconium content of 5 wt%, and the remaining component is attapulgite-based titanium silicalite, and is numbered D4.
[0087] Comparative Example 5
[0088] Preparation of comparative catalysts
[0089] In this comparative example, a catalyst was prepared in the same manner as in Example 2, except that the template agent tetrapropylammonium hydroxide was replaced with an equal amount of tetraethylammonium bromide. The obtained catalyst was numbered D5.
[0090] Experimental Example 1
[0091] Structure Determination of Attapulgite-Based Titanium Silica Zeolite Catalyst
[0092] The structure of the carrier attapulgite-based titanium silicalite prepared in Example 1 was analyzed, and the results were as follows:
[0093] See also Figure 1 , in the XRD spectrum of attapulgite-based titanium silicalite Figure 2 The peaks at θ=7.9°, 8.8°, 23.1°, 23.9° and 24.4° correspond to the characteristic crystal planes (101), (200), (501), (303) and (313) of MFI structured titanium silicate zeolite, proving that titanium silicalite material can be successfully prepared using attapulgite as the silicon source.
[0094] See also Figure 2 In the FTIR spectrum of attapulgite-based titanium silicalite, at 3452 cm -1 The broad band near 1631 cm-1 is attributed to the stretching vibration of -OH in titanium silicalite, while -1 The obvious peak at 450 cm -1 The peak at 1100 cm-1 is attributed to the internal asymmetric Si-O-Si bending vibration. -1 and 798cm -1The position is related to the external symmetric Si-O-Si bond bending vibration mode. For titanium silicalite, 1229 cm -1 and 549cm -1 The nearby bands belong to the double five-membered ring vibration of TiO4 and SiO4 in the MFI topology. In addition, 983cm -1 The peaks near 340 nm correspond to the stretching vibrations of Si-O-Ti bonds in the MFI topology. FTIR spectra further prove that the attapulgite-based titanium silicalite with MFI topology was successfully synthesized.
[0095] See also Figure 3 According to the IUPAC classification, the attapulgite-based titanium silicalite exhibits type I and type IV isotherms and has an H4 type hysteresis loop. This indicates that the synthesized attapulgite-based titanium silicalite has a composite pore consisting of ordered micropores and mesopores formed by zeolite layer stacking.
[0096] See also Figure 4 At the same time, the specific surface area, pore volume and pore size of attapulgite and attapulgite-based titanium silicalite were measured. The results are shown in Figure 1. Compared with the attapulgite raw material, the specific surface area of attapulgite-based titanium silicalite is significantly increased, and its pore size is transformed from a mesoporous structure to an ordered micro-mesoporous structure, showing a pore size distribution concentrated at 2.1 nm, which further proves the existence of this microporous-mesoporous composite pore structure, which is beneficial to promote the dispersion of active metals on the surface of the carrier and promote reaction mass transfer.
[0097] Table 1
[0098]
[0099] Note: A1 is attapulgite; A2 is attapulgite after acid treatment; A3 is attapulgite-based titanium silicalite.
[0100] Electron paramagnetic resonance detection was performed on the attapulgite-based titanium silicalite prepared in Example 1, the C1 catalyst, and the D1 catalyst prepared in Comparative Example D1. The results are as follows:
[0101] See also Figure 5 , the EPR signal at g = 2.003 corresponds to the presence of oxygen defect sites. The signal intensity of the C1 catalyst is significantly greater than that of D1 and attapulgite-based titanium silicalite, confirming that the doping of lanthanide metals promotes the formation of a large number of oxygen defect sites, and the oxygen-rich vacancies can adsorb the intermediates in the reaction process in a specific way, which is conducive to promoting the formation of the target product.
[0102] The final product of step S3 of the preparation process of Comparative Example 5 was measured, and the results were as follows:
[0103] See also Figure 6, and its XRD spectrum did not show the titanium silicate zeolite structure, indicating that after replacing the template, the attapulgite-based titanium silicalite was not successfully synthesized.
[0104] Experimental Example 2
[0105] Performance test of catalyst for catalytic depolymerization of lignin to prepare guaiacol
[0106] Test method: Weigh 1g lignin, 0.1-0.5g catalyst, 10-30ml water and glycerol, 0.1-0.5ml formic acid mixed solution and add it to the autoclave, where the volume ratio of water to glycerol is 1:1-6; fill with 0.1-0.5MPa initial nitrogen pressure, then heat to 270-350℃ within 30min, stir at 500r / min, and seal for reaction for 3-12h. After the reaction is completed, put it in water to cool, then extract the reaction product with ethyl acetate, and then separate the liquid to obtain the ethyl acetate layer after static stratification. Then pass the ethyl acetate layer through a chromatography column containing anhydrous sodium sulfate to remove the incompletely separated water, and finally remove the ethyl acetate by rotary evaporation at a temperature of 45℃ and a speed of 70r / min, and quantitatively analyze the rotary evaporation product. The specific reaction conditions and results are shown in Table 2.
[0107] Table 2
[0108]
[0109] From the above results, it can be concluded that in the absence of an additional hydrogen source, the catalyst of the present invention can achieve full conversion of lignin in a water, glycerol and formic acid solvent system, achieving a 100% lignin conversion rate, wherein the guaiacol yield exceeds 25%, and the guaiacol product yield exceeds 75%.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst, characterized in that: The invention comprises a carrier and an active component loaded on the carrier, wherein the carrier is attapulgite-based titanium silicalite, and the active component is cobalt and lanthanide metal.
2. The lanthanide metal-modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 1, characterized in that: The content of cobalt is 10wt%, the content of lanthanide metal is 1-10wt%, and the balance is attapulgite-based titanium silicalite.
3. The method for preparing the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1. Add the acid-treated attapulgite into a tetrapropylammonium hydroxide aqueous solution and stir to obtain a colorless transparent solution, which is referred to as solution A. Tetrabutyl titanate was added to isopropanol, and after mixing evenly, tetrapropylammonium hydroxide aqueous solution was added and stirred to obtain a colorless transparent solution, which was recorded as solution B; S2, mixing solution A and solution B, first stirring, then heating to remove alcohol, and then adding water for stirring and aging to obtain an aged mixture; S3, crystallizing the aged mixture, washing, drying and calcining the obtained product to obtain attapulgite-based titanium silicalite; S4, mixing the cobalt precursor salt, the lanthanide metal precursor salt, the attapulgite-based titanium silicalite and the solvent, first stirring, then evaporating the solvent and drying, and finally calcining to obtain the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst.
4. The method for preparing the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 3, characterized in that: In step (1), the mass volume ratio of the acid-treated attapulgite, tetrabutyl titanate and tetrapropylammonium hydroxide is 1 g: 0.1-0.5 ml: 2.5-5 g.
5. The method for preparing the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 3, characterized in that: In step (2), the stirring treatment time is 1 to 2 hours; the heating temperature for removing alcohol is 80 to 90° C., and the time is 1 to 2 hours; and the stirring aging treatment time is 12 to 24 hours.
6. The method for preparing the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 3, characterized in that: In step (3), the crystallization treatment conditions are a temperature of 150°C to 200°C and a time of 24 to 36 hours; the specific process of the calcination treatment is: heating the temperature in an air atmosphere at a rate of 1 to 5°C / min to 550 to 700°C, and then calcining at this temperature for 5 to 10 hours.
7. The method for preparing the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 3, characterized in that: In step (4), the stirring treatment is carried out at room temperature for 6 to 12 hours; and the drying treatment is carried out at a temperature of 80 to 110° C. for 12 to 24 hours.
8. The method for preparing the lanthanide metal modified cobalt / attapulgite-based titanium silicalite catalyst according to claim 3, characterized in that: In step (4), the specific process of the calcination treatment is: heating the temperature to 500-700°C at a heating rate of 1-5°C / min in an air atmosphere, and then calcining at this temperature for 5-10 hours.
9. Use of the lanthanide metal-modified cobalt / attapulgite-based titanium silicalite catalyst as claimed in claim 1 or 2 in catalyzing the depolymerization of lignin to prepare guaiacol.
10. A method for preparing guaiacol by depolymerizing lignin, characterized in that: The following steps are involved: Lignin, water, glycerol, formic acid and the catalyst as claimed in claim 1 or 2 are put into a reactor, and nitrogen is filled in the reactor to perform a sealed reaction.
Citation Information
Patent Citations
Catalytic biomass conversion methods, catalysts, and methods of making the same
CA2928831A1
Method for preparing aromatic compound by catalytic hydrocracking of lignin
CN101768052A
Attapulgite-based ordered microporous zeolite catalyst as well as preparation method and application thereof
CN114308042A
Cobalt-zirconium / sepiolite catalyst and preparation method and application thereof
CN116116415A
Attapulgite-derived nickel-titanium lamellar mesoporous catalyst as well as preparation method and application thereof
CN116422366A